Pouvoir, efficacité et symbolisation de la parole incantatoire dans Le Printemps de la liberté de Camara Nangala - Abraham GBOGBOU (Revue Hybrides)
The distinction between language, speech and language, based on the work of Ferdinand de Saussure, has given rise to a linguistics of speech. This studies speech as the individual production of discourse. Here, we are talking about incantatory speech. Speech that puts the African in direct contact with the invisible world. The pragmatic and semiological interpretations we made of the statements in the corpus revealed that incantatory speech is special in its kind. It is endowed with immeasurable power and efficacy, but it becomes a symbol through a process that relies on the word itself. We therefore assume that the incantatory or African word is in itself a mystery worthy of study, but a precious gift given to Africans by Nature to find solutions to the most crucial problems undermining our world, such as incurable diseases.